You're (Not) Welcome: The Impact of Symbolic Boundaries, Intergroup Contact, and Experiences With Discrimination on Immigration Attitudes. (April 2018) - Neumann, Rico; Moy, Patricia
Against the backdrop of Europe's migrant crisis, this study investigates attitudes toward immigrants and immigration policy. Specifically, how do Europeans' attitudes stem from: (a) the symbolic boundaries they draw regarding immigrants (i.e., their perceptions of what constitutes an immigrant); (b) their contact with racially and ethnically different others; and (c) their own experiences with discrimination? Data from the 2014-2015 European Social Survey ( N = 37, 623) show Europeans' symbolic boundaries regarding immigrants varied by respondents' sociodemographics, consumption of political news, and social trust. Most, but not all, forms of intergroup contact enhanced support for specific groups and broader immigration policy. Contrary to expectations, experience with discrimination did not shape attitudes toward specific immigrant groups. Our discussion focuses on theoretical implications, future research, and how findings can inform contemporary public discourse about the migrant crisis.